São Paulo city: Permanent Skills Improvement Course for elected representatives to the Municipal Health Councils - Bógus, Cláudia Maria; Martins, Cleide Lavieri; Dimitrov, Pedro; Fortes, Paulo Antonio de Carvalho; Capucci, Paulo Fernando; Nemes Filho, Alexandre; Escrivão Junior, Álvaro; Siqueira, Arnaldo Augusto Franco de; Telesi Junior, Emilio; Donini, Osvaldo; Elias, Paulo Eduardo Mangeon (Saúde e Sociedade, 2003)
The popular health movement from São Paulo City has been electing Popular Health Councils since 1979. The issue of political and technical capabilities of its leaders has been an important point for the movement. During the years 1993 to 2000, the communication channels between the municipal government and popular leadership have been broken, leading back the social movement related to public health. However, in the beginningof 1988, the organized health movements located both at the east and southeast parts of São Paulo City, were succeeded in electing 1.039 members for those popular councils. After several scattered efforts to provide capability and skills to the councilors, it was decided to join the different regions and movements in only one project named Permanent Skills Improvement Course for elected representatives to the municipal health councils. The Ministry of Health and the Center for Permanent Education of the School of Public Health of Public Health of the University of São Paulo, Brazil, sponsored the initiative, with an amount of 52 courses attended by 1.011 councilors. This article contains both a description of the course process and the councilors social profiles, besides theirs evaluation over the initiative.